The Analysis of Social Impact of Indonesia Teaching Fellowship (ITF) Teacher Training Program By Ruangguru and Bakti Kominfo in Sorong Using the Social Return on Investment (SROI) Method - Dibyana Galih Prakasita; Indra Lestari Fawzi (Journal Research of Social Science, Economics, and Management, 2022)
Indonesian Teaching Fellowship (ITF) teacher training program by Ruangguru and BAKTI Kominfo is a form of contribution from the private sector and the government in improving the quality of education, especially in Sorong, West Papua. This study is to determine and analyze the impact of the program through the Social Return on Investment (SROI) method. The ITF program in Sorong Regency targets 3 main aspects, namely pedagogy, personality, and social. To improve pedagogic abilities, the program provides learning modules through the Ruangguru application as well as online discussions with facilitators; to improve teacher personality, the program provides teacher motivation and personality training by trainers, psychological webinar series, and counseling services; and to improve social skills, the program carries out structured social assistance offline, this activity produces teachers who are ready to go into their communities so that they can expand the impact of the program in Sorong itself. Based on the impact assessment of the ITF program, an SROI Ratio of 1:2.62 was obtained, meaning that for every investment of Rp.1, - an impact or benefit of Rp.2,62 is obtained. Social impact analysis through the SROI method is needed for the sustainability of the ITF program in the future.